An interpretative phenomenological analysis of coaches' experiences of working with children with special health care needs at an exercise referral scheme - Foote, Gareth (2011)
This study examines the experiences of a small number of coaches who work on an exercise referral scheme for children with special health care needs (SHCNs) such as attention deficit hyperactivity disorder (ADHD) and autistic spectrum disorders (ASD). Children with SHCNs can face significant barriers to involvement with peers in extracurricular physical activity and sports. These barriers arise due to difficulties directly related to a condition, such as immaturity in motor skills, problems with concentration and impulsivity, and because of the social stigma associated with these difficulties.